Hollywood's Hawaii : Race, Nation, and War - Konzett, Delia Caparoso (Book collections on Project MUSE., 2017)
Hollywood's Hawaii is the first full-length study of the film industry's intense engagement with Hawaii and the South Pacific from 1898 to the present. This book presents a history of cinema that examines Hawaii and the Pacific and its representation in film in the context of colonialism, war, Orientalism, occupation, military buildup, and entertainment.